2011
DOI: 10.1080/14445921.2011.11104345
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Built Heritage: Community, Economy and Environment

Abstract: Heritage protection in Australia was initiated by community groups such as the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Similar to the studies by Maeer [50], Irons [48], Throsby [32], and Mason [34], it can be concluded that only economically evaluating the historic buildings for conservation is insufficient. Thus, non-economic aspects should also be considered in finding and identifying the values influencing the conservation process.…”
Section: Architectural Heritage and Conservationsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar to the studies by Maeer [50], Irons [48], Throsby [32], and Mason [34], it can be concluded that only economically evaluating the historic buildings for conservation is insufficient. Thus, non-economic aspects should also be considered in finding and identifying the values influencing the conservation process.…”
Section: Architectural Heritage and Conservationsupporting
confidence: 78%
“…Irons and Armitage stated that although in Australia, historic buildings are conserved with respect to the latest standards, they are conserved with an economic perspective, and all the values are valued regarding the economic issues. They concluded that other aspects such as environmental, identity, and social values can be considered too [48]. Hubbard showed that the conservation of the historic buildings does not only involve the architectural and archeological aspects.…”
Section: Architectural Heritage and Conservationmentioning
confidence: 99%
“…Except for cultural heritage assets, Irons and Armitage (2011) and Mason (2008) explain that economists are capable of allocating scarce goods, services and other resources in a market efficient frontier paradigm since they morally consider such assets are priceless goods to human kind. Putting a dollar value for the purpose of improving their conservation efforts does not preclude commodification of historic buildings, monuments and sites to the highest bidder (Zancheti 2016).…”
Section: The Economics Of Built Heritage Pricelessnessmentioning
confidence: 99%
“…Putting a dollar value for the purpose of improving their conservation efforts does not preclude commodification of historic buildings, monuments and sites to the highest bidder (Zancheti 2016). The objective is simply to gain an understanding of what the importance of their use and non-use values are to society (Irons and Armitage, 2011) so that policy and decision-makers can create appropriate efforts for sustainable conservation . After all, de la Torre and Mason (2002:03) states: 'It is selfevident that no society makes an effort to conserve what it does not value.'…”
Section: The Economics Of Built Heritage Pricelessnessmentioning
confidence: 99%
See 1 more Smart Citation